Flexible electro-hydraulic power chips - Chao Zhang; Jionghao Chen; Changyi Xu; Tairan He; Xiaolong Zhang; Junhui Zhang; Ximing Sun; Bing Xu; Yi Zhu; Huayong Yang (Nature Communications)
Abstract Emerging soft systems, including soft robots or wearable devices, actuated by fluidic means facilitate a series of inherent benefits, including safe human-robot interactions, lower costs, and adaptability in geometry for manipulating delicate objects. However, existing fluidic soft systems are facing a critical barrier: how to get rid of traditional rigid, bulky, and redundant fluid power/control components as well as develop their own flexible, portable, and universal fluidic components for implementing fully flexible, multi-circuit, and untethered autonomous systems. Here, we introduce a strategy of flexible electro-hydraulic power chips that enables multi-circuit independent pumping and control of soft systems in simple, compact, and lightweight forms. These electro-hydraulic power chips could be arbitrarily programmed through “line-plane-body” combinations of electro-hydraulic power “diode” or “triode” modules with high output density of 10.77 kPa/g and 2.15 L/min/g, and freely fabricated into the desired shapes and functions via multi-material 3D printing technique. Demonstrations of multi-circuit mass transfer, five-finger selective cooling, bird’s multiple actuation, jellyfish’s fast swimming show electro-hydraulic power chips’ portable, powerful, and multi-circuit independent attributes. The proposed strategy is an important advance towards low-cost, mass-manufactured, and standard universal fluid power components for the next generation of multi-functional, autonomous soft systems.